Soka Gakkai's human revolution: the rise of a mimetic nation in modern Japan - McLaughlin, Levi (Contemporary Buddhism, 2019)
Soka Gakkai as mimetic nation -- From intellectual collective to religion : a history of Soka Gakkai -- Soka Gakkai's dramatic narrative -- Participating in canon : the formation of sacred texts in a new religion -- Cultivating youth : discipleship through standardized education -- Good wives, wise mothers, and foot soldiers of conversion